Imam Maturidi: Obstacles in Hidaya - Bicer, Ramazan; Abdullayev, Nurzhan (ҚазҰУ Хабаршысы. Дінтану сериясы, 2019)
Hidayah is the result of the Will of Allah and His slave. Hidayah is considered to be one of the most important topics in Islam and scholars unanimously agreed that psychological factors would have an influence during the implementation of hidayah. In this article, we have scientifically discussed the obstacles in hidayah, based on the works of Abu Mansur al-Maturidi. As a result, we have widely discussed obstacles which could prevent human beings from reaching hidayah and factors that may have an effect on it. Therefore, the main purpose of the article is to provide thorough explanation about the subject matter. Abu Mansur al-Maturidi, among the scholars of Ahlus Sunnah, has explained the subject matter based on Kalam. Considering specific human characteristics in hidayah, he has shown that functions of the heart could potentially prevent one to reach higher levels of faith (imaan). More broadly, based on the works of Abu Mansur al-Maturidi, we have provided our readers with rigorous description of hidayah itself. Regarding to the explanations of Quran and others works of Abu Mansur al-Maturidi, the fallacy of human knowledge directly effects on the heart. Moreover, belief could lead to the connection of knowledge and heart.